An investigation into native and non-native teachers' assessment of Chinese students' English writing. Issue 2 (2nd April 2020) - Rao, Zhenhui; Liu, Fulan
Abstract: This study compares the assessment criteria which native English-speaking (NES) and non-native English-speaking (NNES) teachers applied in their writing evaluation in a Chinese context. Using both quantitative and qualitative methods, it examines not only how the two groups of teachers assess students' writing holistically, but also how the two groups differ in their analytical reasons for their ratings. The results showed that in holistic evaluation, the NES and NNES teachers differed significantly, with the former assigning higher scores to all the essays. In terms of the analytic evaluation of the ten specifically categorised features, the two groups showed statistically significant differences in four categories. The NES teachers were more lenient in evaluating the categories of 'grammar' and 'sentence structure', but the NNES teachers were less severe in rating the categories of 'ideas' and 'arguments'. An analysis of the findings reveals that the differences in the assessment of students' English writing between the two groups of teachers may originate from their language learning experiences, language teaching methods and language teaching beliefs.